Design, synthesis and biological evaluation of 4-bromo-N-(3, 5-dimethoxyphenyl)benzamide derivatives as novel FGFR1 inhibitors for treatment of non-small cell lung cancer. (1st January 2018) - Xie, Zixin; Cheng, Donghua; Luo, Lu; Shen, Guoliang; Pan, Suwei; Pan, Yaqian; Chen, Bo; Wang, Xuebao; Liu, Zhiguo; Zhang, Yuan; Ye, Faqing
Abstract: A series of 4-bromo-N-(3, 5-dimethoxyphenyl)benzamide derivatives were designed and synthesised as novel fibroblast growth factor receptor-1 (FGFR1) inhibitors. We found that one of the most promising compounds, C9, inhibited five non-small cell lung cancer (NSCLC) cell lines with FGFR1 amplification, including NCI-H520, NCI-H1581, NCI-H226, NCI-H460 and NCI-H1703. Moreover, the IC50 values for the compoundC9 were 1.36 ± 0.27 µM, 1.25 ± 0. 23 µM, 2.31 ± 0.41 µM, 2.14 ± 0.36 µM and 1.85 ± 0.32 µM, respectively. The compoundC9 arrested the cell cycle at the G2 phase in NSCLC cell lines. The compoundC9 also induced cellular apoptosis and inhibited the phosphorylation of FGFR1, PLCγ1 and ERK in a dose-dependent manner. In addition, molecular docking experiments showed that compoundC9 binds to FGFR1 to form six hydrogen bonds. Taken together, our data suggested that the compoundC9 represented a promising lead compound-targeting FGFR1.